Fundamentals of polygraph practice - Krapohl, Donald J.; Shaw, Pamela K.; ScienceDirect eBooks (Amsterdam : Elsevier Ltd., 2015)
Though polygraph has been the mainstay for government and police departments since World War II, it has undergone substantial transformation in recent years. Fundamentals of Polygraph Practice bridges the gap between the outmoded practices and today(u2019)s validated testing and analysis protocols. The goal of this reference is to thoroughly and concisely describe the evidence-based practices of polygraphy. Coverage will include: psychophysiology, testing techniques, data collection, data analysis, ethics, polygraph law, alternate technologies and much more. This text addresses the foundational needs of polygraph students, and is written to be useful and accessible to attorneys, forensic scientists, consumers of polygraph services, and the general public. Includes protocols and fundamentals of polygraph practice Covers the history of lie detection, psychophysiology, data collection, techniques and testing, data analysis and much more Authors are internationally recognized in the polygraph field.
Online resource; title from PDF title page (EBSCO, viewed July 20, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Lie detectors and detection -- Law and legislation; LAW / Criminal Law / General; Lie detectors and detection -- Law and legislation; Electronic books